(untitled) (Texas Journal of Medical Science, 2022)
Asthma is common during childhood when the airways are easily inflamed when in contact with certain allergic triggers. A retrospective study on 80 school-aged children with asthma, the data collected from several different hospitals in Iraq from January 2020 to October 2021 The aim of the study was to find out the prevalence of asthmatic school-aged children in Iraq according to sex and to determine the adaptive capabilities and subjective changes of the patient’s attitude. Quality of life (QOL) criteria were studied according to the WHO questionnaire and coping capacities assessment of children’s activities affected by asthma, overall assessment of the quality of life The results were distributed according to age (Boys from 11-13 years for 19 (47.5%), for girls 20 (50%) and from 14-17 for boys 21 (52.5%), girls 20 (50%) When analysing the effects of asthma according to gender in children, we noticed that there is a predominance in the negative effects of males, and according to Outcomes of children’s activities affected by asthma, Negative results were found in terms of the effect on paediatric patients, with statistical relationships found in most of the variables of this study. We conclude from this study that asthma has an impact on society as well as the affected child may be forced to miss school days. Asthma poses a serious challenge to public health with high direct and indirect costs, while the costs of not treating asthma are much higher. Moreover, asthma has significant effects on patients’ performance at school and work, and this requires concerted efforts in the field of public health, basic and clinical research, and awareness-raising. The general public needs to cope with this growing prevalence.